Isolation and characterization of an H9N2 influenza virus isolated in Argentina - Xu, Kemin (2012)
As part of our ongoing efforts on animal influenza surveillance in Argentina, an H9N2 virus was isolated from a wild aquatic bird (Netta peposaca), A/rosy-billed pochard/Argentina/CIP051-559/2007 (H9N2) - herein referred to as 559/H9N2. Due to the important role that H9N2 viruses play in the ecology of influenza in nature, the 559/H9N2 isolate was characterized molecularly and biologically. Phylogenetic analysis of the HA gene revealed that the 559/H9N2 virus maintained an independent evolutionary pathway and shared a sister-group relationship with North American viruses, suggesting a common ancestor. The rest of the genome segments clustered with viruses from South America. Experimental inoculation of the 559/H9N2 in chickens and quail revealed efficient replication and transmission only in quail. Our results add to the notion of the unique evolutionary trend of avian influenza viruses in South America. Our study increases our understanding of H9N2 viruses in nature and emphasizes the importance of expanding animal influenza surveillance efforts to better define the ecology of influenza viruses at a global scale.